Basic Disorders Of The Central Nervous System - Shermatova Yakutkhan (Genius Journals, 2025)
This article proposes that motor function disorders are most often caused by disorders of the nervous system, that is, disorders of the peripheral nerves, spinal cord, and brainstem. The motor system is located in the frontal lobe of the cerebral cortex.
Keywords: Movement functions; movement disorders; Functional movement